2017
DOI: 10.1002/chem.201703607
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional Fluorogenic Rhodamine Probe for Proximity‐Induced Bioorthogonal Chemistry

Abstract: Bioorthogonal reactions have emerged as a versatile tool in life sciences. The inverse electron demand Diels-Alder reaction (DA ) stands out due to the availability of reactants with very fast kinetics. However, highly reactive dienophiles suffer the disadvantage of being less stable and prone to side reactions. Herein, we evaluate the extent of acceleration of rather unreactive but highly stable dienophiles by DNA-templated proximity. To this end, we developed a modular synthetic route for a novel bifunctiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…While we used BCN as dienophile for in vitro characterization due to its formation of a single product, we tested both, BCN and trans-cyclooctene (TCO) as dienophiles in live cells. TCO derivatives have been reported to possess superior kinetics over BCN [37][38][39] and it is further known that the choice of the DAinv-dienophile can influence the fluorescence turn-on of tetrazine dyes 26,40,41 .…”
Section: Resultsmentioning
confidence: 99%
“…While we used BCN as dienophile for in vitro characterization due to its formation of a single product, we tested both, BCN and trans-cyclooctene (TCO) as dienophiles in live cells. TCO derivatives have been reported to possess superior kinetics over BCN [37][38][39] and it is further known that the choice of the DAinv-dienophile can influence the fluorescence turn-on of tetrazine dyes 26,40,41 .…”
Section: Resultsmentioning
confidence: 99%
“…The chemistries that have been successfully used for template-directed ligations include native chemical ligation, [37] selenocystine-selenoester ligation, [38] phosphorothioate-based ligation, [39][40][41] electrophilic phosphorothioester-based ligation, [42] tetrazine-based ligation, [43][44] and others (Scheme 2.4). These techniques have been used for RNA imaging in bacterial cells [40] , human cells [41,44] , and cell lysates.…”
Section: Oligonucleotide-templated Reactions For Nucleic Acid Detectionmentioning
confidence: 99%
“…[38] However, product inhibition of turnover in template remains a major challenge, despite the successful attempts to alleviate it by the introduction of destabilizing linker at the ligation site. [37,[45][46] the thioester and iso-cysteine [37] ; b) selenocystine-selenoester ligation [38] ; c) phosporothioate-based ligation [39][40] ; d) electrophilic prosphorothioester-based ligation [42] ; e) tetrazine-based ligation reported by Seckute et al [44] and f) tetrazinebased ligation reported by Werther et al [43] Transfer-based OTR relocates a functional unit such as a quencher [15,[47][48] or a fluorophore [49] from one reactive probe to another (Scheme 2.5a and a`).…”
Section: Oligonucleotide-templated Reactions For Nucleic Acid Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCF8 was coupled to amine‐terminated ODN1 (NH 2 ‐ODN1) to afford nonfluorescent SCF8‐ODN1, which was then utilized in an ODN‐templated fluorogenic Heck reaction with vinyl‐functionalized ODN2 (ODN2‐vinyl; Figure ) . Other types of hetero‐bifunctional SCF linkers (SCF9‐SCF12) were also developed for ODN detection through template‐directed fluorogenic ODN ligation reaction (Figure ) …”
Section: Fluorogenic Bifunctional Linkersmentioning
confidence: 99%